Preclinical evaluation of an MR-compatible microwave ablation system and comparison with a standard microwave ablation system in an ex vivo bovine liver model. (18th August 2017) - Hoffmann, Rüdiger; Kessler, David-Emanuel; Weiss, Jakob; Clasen, Stephan; Pereira, Philippe L.; Nikolaou, Konstantin; Rempp, Hansjörg
Abstract: Objective: Evaluation of a newly developed MR-compatible microwave ablation system with focus on ablation performance and comparison with a corresponding standard microwave ablation system. Materials and methods: A total of 52 ablations were performed with a non-cooled microwave ablation system in an ex vivo bovine liver model using the following settings: [A] 16G-standard antenna, 2 cm active tip, 2.4 m cable; [B] MR-compatible 16G-antenna, 2 cm active tip, 2.4 m cable; [C] MR-compatible 16G-antenna, 2 cm active tip, extended 6 m cable; and [D] MR-compatible 16G-antenna, 4 cm active tip, extended 6 m cable. Ablation durations were 3, 5 and 10 min, and additionally 15 min for [D]. Ablations zones were measured for short-axis diameter (SA) and long-axis diameter (LA). Settings [A]–[C] were compared regarding SA, volume (V) and generator energy output (E) with analysis of variance and Tukey–Kramer post hoc test. Ablation performance of the MR-compatible settings [C] and [D] were compared regarding SA, V, E and sphericity index (SA/LA) with unpaired t -test. p  < 0.05 was considered as statistically significant. Results: No significant differences were found between [A], [B] and [C] regarding SA and V (10 min; SA[A] = 25.8 ± 2.4 mm, SA[B] = 25.3 ± 1.9 mm, SA[C] = 25.0 ± 2.0 mm, p  = 0.88; V[A] = 17.8 ± 4.4 cm³, V[B] = 16.6 ± 3.0 cm³, V[C] = 17.8 ± 2.7 cm³, p  = 0.85); however, the highest energy output was measured for setting [C] (10 min; [A]: 9.9 ± 0.5 kJ, [B]: 10.1 ± 0.5 kJ, [C]: 13.1 ± 0.3 kJ, p  < 0.001). SA, V and E were significantly larger with setting [D] than [C] with 10 min ablations (SA[C] = 25.0 ± 2.0 mm, SA[D] = 34.0 ± 2.9 mm, p  = 0.003; V[C] = 17.8 ± 2.7 cm³, V[D] = 39.4 ± 7.5 cm³, p  = 0.007; E[C] = 13.1 ± 0.3 kJ, E[D] = 16.7 ± 0.8 kJ, p  = 0.002) without significant difference in sphericity index (SA/LA[C] = 0.46 ± 0.02, SA/LA[D] = 0.52 ± 0.04, p  = 0.08). Conclusion: The tested MR-compatible system can be used without loss of ablation performance compared to the standard system.